O-025 The Superiority of Thrombectomy over IV rtPA Monotherapy May be Associated with Thrombus Length – Results of the THERAPY Trial. (29th July 2016) - von Kummer, R; Mocco, J; Zaidat, O; Khatri, P; Gupta, R; Frei, D; Lopes, D; Shownkeen, H; Berkhemer, O; Meyer, D; Chauke, M; Hak, S; et al.
Abstract : Introduction: Limited data exist on the efficacy of intra-arterial therapy (IAT) for ischemic stroke resulting from extended thrombi. IV-rtPA has been the staple of ischemic stroke therapy, however the efficacy of IV thrombolytics is known to diminish with increasing thrombus length, subsequently reducing the potential for successful revascularization. For increasing thrombus lengths, the benefits of aspiration thrombectomy have yet to be validated in a large, randomized trial, but may offer advantages over IV rtPA; herein we present our experience of the benefits of aspiration thrombectomy on extended thrombi. Materials and methods: The randomized prospective THERAPY stroke trial assessed the benefits of combined aspiration thrombectomy with adjunctive IV-rtPA compared to IV-rtPA alone in patients with thrombus length ≥8 mm. The associations of thrombus length to primary and secondary endpoints were assessed by univariate and multivariate analyzes, while multiplicative interaction between treatment allocation and thrombus length was assessed by multivariate ordinal regression of 90 day mRS. Results: In total, THERAPY enrolled 108 patients with a median thrombus length of 14.0 mm (IQR 9.7–19.5); all exhibiting large vessel occlusions in the anterior circulation, including the ICA (28%), MCA M1 (62%), and MCA M2 (10%). Analysis revealed longer thrombi to be associated with worse clinical outcomes for all dichotomized endpoints relating to presence of complication relative to median thrombus length (all p < 0.05, except mRS 0–2), and resulted in higher 90 day mRS (p = 0.005). Additionally, longer thrombi also correlated with higher incidence of symptomatic intracranial hemorrhage (p = 0.03), serious adverse events (p = 0.02), and mortality (p = 0.01). Reperfusion to mTICI 2 b-3 had no significant relationship with thrombus length, however procedural time was notably longer for patients with longer thrombi (rho = 0.36, p = 0.045). The relative benefit of IAT was apparent in patients with longer thrombi over thrombolytic monotherapy (p = 0.03; Figure 1 ). Consequently, compared to patients receiving IAT, lytic therapy patients had worse 90 day mRS (rho = 0.20, p = 0.17 for IAT vs 0.39, p = 0.008 for IV-rtPA). Conclusion: Extensive thrombus burden presents a challenge for stroke intervention, posing greater risk of complications and poor clinical outcome. However, this effect is dampened when IAT is the interventional modality, leading to a more favorable prognosis over IV-rtPA alone. This study finding supports the use of aspiration thrombectomy in treatment of extended thrombi, demonstrating relative advantages over thrombolytic monotherapy, and enables better clinical outcomes. Disclosures: R. von Kummer: 2; C; Penumbra, Inc. J. Mocco: 1; C; Penumbra, Inc. O. Zaidat: 6; C; Penumbra, Inc. P. Khatri: 1; C; Penumbra, Inc. R. Gupta: 6; C; Penumbra, Inc. D. Frei: 6; C; Penumbra, Inc. D. Lopes: 6; C; Penumbra, Inc. H. Shownkeen: None. O. Berkhemer: None. D. Meyer: 5; C; Penumbra, Inc. M. Chauke: None. S. Hak: 5; C; Penumbra, Inc. S. Kuo: 5; C; Penumbra, Inc. H. Buell: 5; C; Penumbra, Inc. A. Bose: 4; C; Penumbra, Inc. 5; C; Penumbra, Inc. S. Sit: 4; C; Penumbra, Inc. 5; C; Penumbra, Inc. A. Yoo: 1; C; Penumbra, Inc., National Institute of Health, Remedy Pharmaceuticals.